Evaluation of rheological performance of a local modified bitumen by Styrene Butadiene Styrene polymer used in wearing course (Fracture and Structural Integrity, 2021)
In road construction, bitumen is the binder that gathered the different aggregates of road pavements. Bitumen, as a viscoelastic material, influences considerably the rheological behavior of bitumen concrete.The bitumen used in Algeria, showed its limits face to the traffic, which is increasing continuously. This research aims to valorize SBS polymer in wearing course by modifying a pure 35/50 bitumen. The present paper aims to study the polymer derived from styrene and butadiene (SBS) from the company Kraton Polymers International Ltd in the modification of a bitumen to improve its mechanical characteristics.To this end, the incorporation of SBS polymer was carried out according to two contents: 5.0 and 7.5% (by weight of asphalt), the objective being to evaluate the influence of this type of polymer on the rheological properties of the bitumen ordinary road including viscosity and modulus.The results reveal that the bitumen modified with 7.5% of SBS has better mechanical performance on the rigidity and the elasticity compared to the conventional bitumen. Recommendations have been made to implement a bitumen modification system to improve its quality and therefore the durability of bituminous pavements in the south of Algeria.
Keywords: polymer modified bitumen; rigidity; SBS polymer; thermal susceptibility; dynamic mechanical analysis